Site selection for reclaimed water infiltration using GIS tools - Silva, Flora (2012)
In the Beira Interior region (Portugal) some sources of water do not present characteristics suitable for some uses due to pollution (namely associated to the discharge of point and nonpoint effluents) or are over-exploited (namely the aquifers). However, the water demand will grow in this region to meet socio-economic activities under development (e.g. the Cova da Beira irrigation plan, irrigation of golf courses and green areas and SPAs, as well as for distribution for human and industrial consumption), which will lead to the search of alternative sources of water. The region is characterized by many disperse urban agglomerates with less than 2,000 inhabitants, where the wastewater treatment plants (WWTP) are mainly ecological systems such as constructed wetlands (CW). In this context, the treated wastewater (reclaimed water) from these ecological treatment systems should be seen as a source of water to be used and not a waste to be eliminated. After a monitoring campaign of two years at the CW system of Vila Fernando (Guarda, Portugal), the characteristics of the final effluent suggest that it could be used for aquifer recharge, not only because it is an area that uses many groundwater resources, but because other uses seem to be not relevant and would require a polishing treatment for the effluent, which would increase the costs of both investment and operation. From 6 thematic maps and environmental, technical and economic criteria, it was selected a study area of 6687 ha. This area was analysed based on the manipulation of complex information using Geographic Information Systems (GIS), which consisted on overlapping areas of exclusion and inclusion from each thematic map and the use of algebraic operations (multi-criteria analysis) to obtain a final Suitable Map that indicated an area of 6.4 ha located in anthrosols as the most favorable ones for the infiltration of reclaimed water.